Limits to Wage Growth: Understanding the Wage Divergence between Immigrants and Natives - Apoorva Jain; Klara Sabirianova Peter (Institute of Labor Economics (IZA), 2017)
This study finds evidence of wage divergence between immigrants and natives in Germany using a country-wide household panel from 1984 to 2014. We incorporate the possibility of wage divergence into a two-period model of economic assimilation by modeling the differences in the efficiency of human capital production and prices per unit of human capital between immigrants and natives. Individual rates of wage convergence are found to be higher for immigrants who fled warfare zones, belong to established ethnic networks, and acquired more years of pre-migration schooling. Using a doubly robust treatment effect estimator and the IV method, the study finds that the endogenous post-migration education in the host country contributes substantially to closing the wage gap with natives. The treatment effect is heterogeneous, favoring immigrants who are similar to natives. This paper also addresses the commonly ignored sample selection issue due to non-random survey attrition and employment participation. Empirical evidence favors the "efficiency" over the "discrimination" channels of wage divergence.
Keywords: J15; J24; J31; J61; F22; I26; 330; migration; assimilation; divergence; wage growth; skill prices; post-migration human capital; discrimination; doubly robust estimator; instrumental variables; panel; Germany